Cosmopolitanisms in Muslim Contexts: Perspectives from the Past By Derryl N. Maclean and Sikeena Karmali Ahmed, eds. (Edinburgh: Edinburgh University Press, 2013. 190 pages.) (American Journal of Islam and Society, 2015)
This book is a welcome addition to the ever-expanding literature on Muslimcosmopolitanism across the Islamicate world. Its chief aim is to decenter thelong-held notion that cosmopolitanism was a style of thought that emergedprimarily from the heart of Europe, beginning with the Greeks, and then carriedover into the Enlightenment age of Emmanuel Kant and reached its fullmanifestation in the present moment (p. 2). Rather, “cosmopolitan instances,”which Kai Kreese deftly describes as “openness to the world (Weltoffenheit),experience of the world (Welterfahrung), and the skill to deal flexibly withthe world (Weltgewandtheit)” (p. 33), took root in Muslim societies many centuriesago, particularly during the establishment of the Indian Ocean’s livelymaritime Muslim community during the eleventh century ...